Estimativa do surto de crescimento puberal pela avaliação das vértebras cervicais em radiografias cefalométricas laterais - Armond, Mônica Costa [UNESP] (2000)
The aim of this research was to estimate the skeletal growth and development by observingradiographically the morphological changes of the first, second and third cervical vertebrae, according to the method proposed by Hassel &Farman32 (1995) in patients who were going through the outbreak of pubertal growth. The radiographic inspection of the cervical vertebrae was performed by means of cephalometric radiographs and the outbreak of pubertal growth was identified through the events of ossification of the hand and wrist. For that purpose, we selected thecephalometric radiographs and hand•wrist radiographs of 110 Brazilianleukoderms, male and female,with chronological age ranging from 8 to 14,6 years old for the girls and from 9,5 to 15,4 years old for the boys.The results showed that there was a statistically significant correlation between the maturation indicators of the cervical vertebrae and the patients who were going through the outbreak of pubertal growth. The conclusion was that the radiographic evalution of the changes of the cervical vertebrae, in the cephalometric radiographs, is an alternative parameter, which is reliable and practical in the skeletal evalution, and the it completes the range of information that must be obtained from the patient under orthodontic treatment and that it can, circumstantially, replace other methods of evalution